THE MERITS AND DEMERITS OF HOEY'S MATCHING PATTERNS - Abdul Jabbar, Lubna Riyadh; Hameed, Sarab Khalil (Al-Adab Journal, 2016)
Within the realm of the linguistic description of text, Hoey has adopted the approach that sees text as possessing organization, that is, describable in terms of patterns of organization. Accordingly, organizational statements of text describe what is done by accounting for probabilities. In such an approach, no linguistic combination is impossible, but some are decidedly improbable. Hoey claims that the structural description of text cannot attain perfection in any area of language study, and that the formation of structural principles forces the linguist to consider the exceptions, and thus to discover new regularities through the process of matching patterns. The present study shed some light on the merit and demerits of such an approach and the possibility of applying it in the analysis of texts.